ANALISIS PENDAPATAN USAHA TANI TOMAT DAN KONTRIBUSINYA TERHADAP PENDAPATAN PETANI DI KELURAHAN API-API KECAMATAN BONTANG UTARA - Siti Balkis (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
The purpose of the research was to determine the tomato farm income and knowing the tomato farm income contributing to household incomes of farmers in Api-Api Village, Bontang Utara Sub District.This research started on April until July 2012, with research location is in Api-Api Village, Bontang Utara Sub District.  The method that used is census method. The data needed by research are primary and secondary data. Primary data is got by observation and interview with responder use questionnaire which have been compiled in line with research.  While secondary data is got from bibliography study and institution information which is related to research execution.  The results of this research shows that :Based on the survey result to 9 respondent obtained  tomato production to one season is 4.777,78 kg-1 meter-1 at the price of selling Rp 8.000 – 9.000 kg-1. Total revenue farmers was Rp 730.000.000,00 year-1 and total income from tomato farming is Rp 522.588.633,33 year-1with average farm income is Rp 58.065.403,70 year-1 respondents-1.Value of R/C ratio was 3,45 meaning that the cultivated tomato farm is already profitable then planting a tomato can for resumes.Average contributing of the tomato farm income to household incomes of farmers is 62,50%.